2020
DOI: 10.3390/jcm9103370
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic and Bleeding Events Associated with Thrombocytopenia and Thrombocytosis after Percutaneous Coronary Intervention in Patients with Acute Myocardial Infarction

Abstract: The early and late ischemic and bleeding clinical outcomes according to baseline platelet count after percutaneous coronary intervention (PCI) in patients with acute myocardial infarction (AMI) remain unclear. Overall, 10,667 patients from the Cardiovascular Risk and identification of potential high-risk population in AMI (COREA-AMI) I and II registries were classified according to the following universal criteria on baseline platelet counts: (1) moderate to severe thrombocytopenia (platelet < 100 K/μL, n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 21 publications
0
14
0
1
Order By: Relevance
“…We conducted a prospective cohort study using data from the CardiOvascular Risk and idEntification of potential high-risk population in AMI (COREA-AMI) registry. The details of the registry have been published [ 17 ]. In brief, the COREA-AMI is a prospective, multicenter registry used to evaluate the outcomes of AMI patients in real-world clinical practice and involved consecutive patients (age > 20 years) who presented to nine nation-wide hospitals with a final diagnosis of AMI and were treated with percutaneous coronary intervention (PCI) using stents from January 2004 to August 2014.…”
Section: Methodsmentioning
confidence: 99%
“…We conducted a prospective cohort study using data from the CardiOvascular Risk and idEntification of potential high-risk population in AMI (COREA-AMI) registry. The details of the registry have been published [ 17 ]. In brief, the COREA-AMI is a prospective, multicenter registry used to evaluate the outcomes of AMI patients in real-world clinical practice and involved consecutive patients (age > 20 years) who presented to nine nation-wide hospitals with a final diagnosis of AMI and were treated with percutaneous coronary intervention (PCI) using stents from January 2004 to August 2014.…”
Section: Methodsmentioning
confidence: 99%
“…After a comprehensive search, we identified 19 studies with 217 459 participants 4–9 11–13 28 37–45 Figure 1. illustrates the flow diagram of the search strategy used.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, patients from the included studies adequately represent the population of interest. Study attrition bias was rated as moderate in the studies that did not report percentage of lost to follow-up population 4 6–9 11–13 28 40 45. One study reported 14% missing follow-up data without providing any reasons, that is why this study was regarded as of high risk of attrition bias 43.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations